Kurikulum 2004: Penerapannya dalam Bahan Ajar dan LKS - Endang Mulyani (Universitas Negeri Yogyakarta, 2005)
Recent decades Indonesia education sector lays on the critical context. That critical context attaches at various social aspects influencing to input quality, process and education outcomes. Education quality relates to quality of process and product. Process quality can be achieved if learning process flow effectively and students comprehend fully the learning process. On the other hand that learning process will run well if it is backed up by availability of good learning material and LKS. Curriculum is an escort to run education activities of schools from elementary school to higher education, therefore contains of learning material should not deviate from the curriculum.